PREPARATION OF A SPORTS RESERVE IN HIGHER EDUCATION IN THE FIELD OF PHYSICAL CULTURE AND SPORT - Solovyov, V.B.; Petrov, S.I.; Medvedeva, E.N.; Zakrevskaya, N.G. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the possibilities of a higher education institution of physical culture to carry out activities for the preparation of a sports reserve. Methods and structure of the study. In the course of the work, the federal standards of sports training, implemented in accordance with the Federal State Educational Standards of the program, were analyzed, the conditionality of the training of the sports reserve with personnel, methodological, material and technical resources was revealed. A survey of teachers of the Lesgaft NSU was conducted. Results and conclusions. As the results of the study showed, the universities of physical culture have all the opportunities for training a sports reserve. At the same time, this type of activity entails a number of changes in the educational process. The education system in sports universities should provide training for both high-class athletes and qualified coaches. At present, the model of integrating the training of a sports reserve into the educational process of higher educational institutions of physical culture is becoming more and more in demand, where the normative support of the training system is carried out on the basis of the Federal Standard of Sports Training by sport.